High-voltage-resistant lithium ion negative pole piece and lithium ion battery
By using graphite of a specific particle size to grading with silicon material in the negative electrode sheet of a lithium-ion battery, and forming a double-layer coating structure and rolling process, the problem of silicon negative electrode material due to poor volume expansion and electrical conductivity is solved, and the voltage resistance and stability of the battery are improved.
Patent Information
- Application Number
- CN202411662128.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
AI Technical Summary
At this stage, the silicon negative electrode material has limited its application in lithium-ion batteries due to its large volume expansion, low compaction density and poor electrical conductivity.
By grading graphite with a specific particle size with a specific particle size silicon material and forming a double-layer coating structure in the electrode sheet, the compaction density and pressure resistance of the electrode sheet are improved in combination with the rolling process.
The voltage withstandability and dynamic performance of the negative electrode sheet of lithium-ion battery is improved, the expansion of the negative electrode of silicon is reduced, and the stability of the overall battery is improved.
Smart Images

Figure CN119581488A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a high-voltage lithium ion negative electrode plate and a lithium ion battery. Background Art
[0002] With the development of science and technology, lithium-ion batteries are widely used in various electronic devices and electric vehicles due to their high energy density, long cycle life and environmental protection. The theoretical capacity of pure silicon material is as high as 4200mAh / g, which is about ten times that of graphite negative electrode, and is widely used in negative electrode materials of lithium-ion batteries. However, the volume change of silicon material exceeds 300% during the process of lithium insertion and extraction, which will cause it to fall off the current collector very easily; at the same time, the silicon material itself is not pressure-resistant, and it will break under high compaction during the production of the pole piece, resulting in a sharp decline in battery performance. In summary, at this stage, the application of silicon negative electrode materials is greatly limited due to defects such as large expansion, low compaction density and poor conductivity. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a high-voltage lithium-ion negative electrode plate.
[0004] Another technical problem solved by the present invention is to provide a lithium-ion battery using the above-mentioned high-voltage lithium-ion negative electrode plate.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A high-voltage lithium-ion negative electrode plate is prepared by the following method:
[0007] (1) slurrying graphite and silicon materials according to the mixing ratio of the first coating 1 and the second coating 2, respectively, wherein the raw material of the first coating 1 is composed of graphite, silicon, a binder and a conductive agent, and the mass ratio of graphite + silicon: binder: conductive agent is 85-97: 2-8: 0.1-7; the raw material of the second coating 2 is composed of graphite, silicon, a binder and a conductive agent, and the mass ratio of graphite + silicon: binder: conductive agent is 85-96: 2-10: 0.1-5; the mass ratio of graphite to silicon is 68-83: 9-24;
[0008] (2) forming a first coating layer 1 and a second coating layer 2 on the current collector 3 by a double-layer coating method, wherein the second coating layer 2 is located between the current collector 3 and the first coating layer 1;
[0009] (3) Compact the electrode through a rolling process.
[0010] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the graphite in step (1) uses graphite secondary particles, and the particle size distributions of D10, D50, and D90 of the graphite secondary particles are 6 μm < D10 < 12 μm, 15 μm < D50 < 17 μm, and 35 μm < D90 < 37 μm respectively. The particle size distributions of D10, D50, and D90 of the silicon particles are 4 μm < D10 < 5 μm, 6 μm < D50 < 9 μm, and 10 μm < D90 < 13 μm respectively.
[0011] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the silicon raw material in step (1) is spherical / spheroidal silicon with a conductive agent coating on its surface.
[0012] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the spherical / spheroidal silicon with a conductive agent coating on its surface is prepared by the following process: Porous carbon is subjected to CVD (gas-phase) silicon deposition, and then carbon coating is carried out to prepare a spherical / spheroidal silicon negative electrode; a conductive agent coating is carried out on the surface of the prepared silicon negative electrode.
[0013] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the mass ratio of the graphite to the silicon is 76:18.
[0014] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the mass ratio of graphite + silicon: binder: conductive agent in the first coating 1 is 96.73:3.04:0.23.
[0015] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the mass ratio of graphite + silicon: binder: conductive agent in the second coating 2 is 96.39:3.38:0.23.
[0016] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the conductive agent includes but is not limited to carbon nanotubes (CNT) or linear nano-carbon conductive agents.
[0017] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the binder is composed of PAA (polyacrylic acid), CMC-Li (lithium carboxymethyl cellulose), and SBR (styrene-butadiene rubber), and the mass ratio of PAA, CMC-Li, and SBR is (10 - 49):(10 - 45):(51 - 90).
[0018] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the mass ratio of PAA, CMC-Li, and SBR is 1:1:2.
[0019] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the material of the negative electrode current collector 1 includes but is not limited to metal foil materials or polymer composite foil materials.
[0020] Preferably, for the above high-voltage-resistant lithium-ion negative electrode sheet, the material of the current collector 1 is copper foil.
[0021] Preferably, in the above-mentioned high-voltage lithium-ion negative electrode plate, the foil thickness of the current collector 1 is 4-15 μm.
[0022] Preferably, for the above-mentioned high-voltage lithium-ion negative electrode plate, the compaction density in step (3) is 1.62-1.71.
[0023] Preferably, for the above-mentioned high-voltage lithium-ion negative electrode plate, the compaction density in step (3) is 1.66-1.71.
[0024] A lithium ion battery uses the high-voltage lithium ion negative electrode plate as the negative electrode plate of the battery.
[0025] Preferably, the above lithium-ion battery is prepared by the following method:
[0026] 1) After the rolled positive electrode sheet and negative electrode sheet are cut and cut, the electrode tabs are welded to prepare the positive electrode sheet and negative electrode sheet to be wound;
[0027] 2) preparing an electrode group by winding the prepared positive electrode sheet, negative electrode sheet and separator;
[0028] 3) Encapsulate the electrode group in an aluminum-plastic shell for bilateral encapsulation;
[0029] 4) Dry the electrode group, test the electrode group for moisture, and then inject liquid;
[0030] 5) The electrode group after liquid injection is packaged, aged at room temperature for 36 hours, and subjected to formation, hot pressing, and capacity separation processes to complete the preparation of the battery.
[0031] Beneficial effects:
[0032] The high-voltage lithium-ion negative electrode plate adopts a specific particle size of graphite and a specific particle size of silicon material particle size grading, optimizes the low-expansion and high-compactness negative electrode material and formula, and adopts a specific particle size of graphite and a spherical (spherical) silicon negative electrode coated with a conductive agent for particle size grading, which can not only improve the dispersion uniformity, improve the compaction density of the electrode plate, and improve the pressure resistance of the electrode plate, but also reduce the expansion of the silicon negative electrode, thereby improving the overall battery The dynamic performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of a quasi-spherical / spherical silicon negative electrode with a conductive agent coated on the surface.
[0034] Figure 2 Schematic diagram of double-layer coating.
[0035] Figure 3 SEM image of particle integrity.
[0036] Figure 4 It is a magnification performance graph.
[0037] Figure 5 It is a cyclic performance curve graph.
[0038] In the figure: 1 - the first coating; 2 - the second coating; 3 - the current collector Specific embodiments
[0039] The following will make a detailed description of the high - voltage - resistant lithium - ion negative electrode sheet of the present invention in combination with the embodiments and the drawings.
[0040] Embodiment 1
[0041] As Figure 1-2 shown, the high - voltage - resistant lithium - ion negative electrode sheet is prepared by the following method:
[0042] (1) Pulp is prepared for graphite and silicon materials respectively according to the mixing ratio of the first coating 1 and the second coating 2. Among them, the raw materials of the first coating 1 are composed of graphite, silicon, binder, and conductive agent CNT. The mass ratio of graphite + silicon: binder: conductive agent is 96.73:3.04:0.23; the raw materials of the second coating 2 are composed of graphite, silicon, binder, and conductive agent CNT. The mass ratio of graphite + silicon: binder: conductive agent is 96.39:3.38:0.23; the mass ratio of graphite and silicon is 76:18; the binder is composed of PAA, CMC - Li, and SBR, and the mass ratio of PAA, CMC - Li, and SBR is 1:1:2; the graphite uses graphite secondary particles, and the particle size distributions of D10, D50, and D90 of the graphite secondary particles are 6μm < D10 < 12μm, 15μm < D50 < 17μm, and 35μm < D90 < 37μm respectively. The particle size distributions of D10, D50, and D90 of the silicon particles are 4μm < D10 < 5μm, 6μm < D50 < 9μm, and 10μm < D90 < 13μm respectively; the silicon raw material in the first coating 1 and the second coating 2 is spherical / spherical silicon with a conductive agent coated on the surface, which is prepared by the following process: Porous carbon undergoes CVD (gas - phase) silicon deposition, and then carbon coating is carried out to prepare spherical / spherical silicon negative electrode; CNT coating of the conductive agent is carried out on the surface of the prepared silicon negative electrode;
[0043] (2) A 10 - μm copper foil is used as the current collector, and the first coating 1 and the second coating 2 are simultaneously formed on the current collector 3 by a double - layer coating method, where the second coating 2 is located between the current collector 3 and the first coating 1;
[0044] (3) The electrode sheet is compacted through a rolling process, and the compaction density is 1.66.
[0045] Embodiment 2
[0046] The high-voltage-resistant lithium-ion negative electrode sheet is prepared by the following method:
[0047] (1) Pulp the graphite and silicon materials respectively according to the mixing ratio of the first coating 1 and the second coating 2. Among them, the raw materials of the first coating 1 are composed of graphite, silicon, a binder, and a linear nano-carbon conductive agent. The mass ratio of graphite + silicon: binder: conductive agent is 85:2:7; the raw materials of the second coating 2 are composed of graphite, silicon, a binder, and a linear nano-carbon conductive agent. The mass ratio of graphite + silicon: binder: conductive agent is 85:2:5; the mass ratio of graphite to silicon is 68:24; the binder is composed of PAA, CMC-Li, and SBR, and the mass ratio of PAA, CMC-Li, and SBR is 10:10:90; the graphite uses graphite secondary particles, and the D10, D50, and D90 particle size distributions of the graphite secondary particles are 6μm < D10 < 12μm, 15μm < D50 < 17μm, and 35μm < D90 < 37μm respectively. The D10, D50, and D90 particle size distributions of the silicon particles are 4μm < D10 < 5μm, 6μm < D50 < 9μm, and 10μm < D90 < 13μm respectively; the silicon raw material in the first coating 1 and the second coating 2 is spherical / spherical silicon with a conductive agent coated on the surface, which is prepared by the following process: Perform CVD (gas-phase) silicon deposition on porous carbon, and then perform carbon coating to prepare spherical / spherical silicon negative electrode; Coat a linear nano-carbon conductive agent on the surface of the prepared silicon negative electrode;
[0048] (2) Use a 4μm copper foil as the current collector, and simultaneously form the first coating 1 and the second coating 2 on the current collector 3 by a double-layer coating method, where the second coating 2 is located between the current collector 3 and the first coating 1;
[0049] (3) Compact the electrode sheet through a rolling process, and the compaction density is 1.62.
[0050] Example 3
[0051] The high-voltage-resistant lithium-ion negative electrode sheet is prepared by the following method:
[0052] (1) Pulp is prepared from graphite and silicon materials respectively according to the mixing ratio of the first coating 1 and the second coating 2. Among them, the raw materials of the first coating 1 are composed of graphite, silicon, binder and conductive agent CNT. The mass ratio of graphite + silicon: binder: conductive agent is 97:8:0.1; the raw materials of the second coating 2 are composed of graphite, silicon, binder and conductive agent CNT. The mass ratio of graphite + silicon: binder: conductive agent is 96:10:0.1; the mass ratio of graphite and silicon is 83:9; the binder is composed of PAA, CMC-Li and SBR, and the mass ratio of PAA, CMC-Li and SBR is 49:45:51; the graphite uses graphite secondary particles, and the particle size distributions of D10, D50, and D90 of the graphite secondary particles are 6μm < D10 < 12μm, 15μm < D50 < 17μm, and 35μm < D90 < 37μm respectively. The particle size distributions of D10, D50, and D90 of the silicon particles are 4μm < D10 < 5μm, 6μm < D50 < 9μm, and 10μm < D90 < 13μm respectively; the silicon raw material in the first coating 1 and the second coating 2 is spherical / spherical silicon with a conductive agent coated on the surface (the same as in Example 1).
[0053] (2) A 15μm copper foil is used as the current collector, and the first coating 1 and the second coating 2 are simultaneously formed on the current collector 3 by a double-layer coating method. Among them, the second coating 2 is located between the current collector 3 and the first coating 1.
[0054] (3) The electrode sheet is compacted through a rolling process, and the compaction density is 1.71.
[0055] Example 4
[0056] Comparison data of different schemes: Comparison is carried out from four aspects: compaction density, electrode sheet thickness expansion rate, rate performance and cycle performance. Among them,
[0057] 1 Electrode sheet adhesion: It directly reflects the adhesion effect between the active material on the battery electrode sheet and the current collector copper / aluminum; if the adhesion strength is too low, as the active material expands during cycling, it will break away from the current collector and become electrically inactivated, accelerating the battery decay. It is mainly affected by the binder.
[0058] 2 Thickness expansion rate: There is electrode sheet rebound after rolling of the silicon negative electrode sheet, and thickness expansion will occur after charge and discharge cycling. The thickness expansion rate is used to measure. The lower the thickness expansion rate, the better the battery performance.
[0059] 3 Rate performance and cycle performance: Rate performance is an important parameter for evaluating kinetics. The better the rate performance, the better the kinetic performance. Cycling is an important parameter for evaluating the stability of the battery. The flatter the cycling trend, the more stable the system.
[0060] The detailed scheme is as follows:
[0061] Specific preparation process of the negative electrode sheet in Solution 1:
[0062] 1) Graphite with a secondary particle size distribution of 6 μm < D10 < 12 μm, 15 μm < D50 < 17 μm, and 35 μm < D90 < 37 μm is size-graded with silicon having a particle size distribution of 4 μm < D10 < 5 μm, 6 μm < D50 < 9 μm, and 10 μm < D90 < 13 μm. The morphology of the silicon is amorphous silicon negative electrode. For the first coating 1: The raw materials include graphite, silicon, a binder (composed of PAA, CMC-Li, and SBR in a mass ratio of 1:1:2), and a conductive agent CNT. The mass ratio of graphite + silicon (graphite:silicon mass ratio 76:18):binder:conductive agent CNT is 96.73:3.04:0.23 for homogenization; for the second coating 2: The raw materials include graphite, silicon, a binder (composed of PAA, CMC-Li, and SBR in a mass ratio of 1:1:2), and a conductive agent CNT. The mass ratio of graphite + silicon (graphite:silicon mass ratio 76:18):binder:conductive agent CNT is 96.39:3.38:0.23 for homogenization. A 10-μm copper foil is used as the current collector, and the prepared slurry is coated on the current collector 3 in a double-layer coating method to simultaneously form the first coating 1 and the second coating 2. As Figure 2 shown, the second coating 2 is located between the current collector 3 and the first coating 1;
[0063] 2) After the coated electrode sheet is rolled at a compaction density of 1.62, it is subjected to processes such as slitting and blanking, and the tab is welded to prepare the negative electrode sheet to be wound.
[0064] For Solutions 2 and 3, refer to Solution 1. The difference lies in: the compaction density is different. The compaction density of Solution 2 is 1.66, and the compaction density of Solution 3 is 1.71.
[0065] For Solution 4, refer to Solution 1. The difference lies in: the silicon negative electrode is spherical-like (spherical), and the compaction density is 1.66.
[0066] For Solution 5, refer to Solution 1. The difference lies in: the silicon negative electrode is spherical-like (spherical), and the compaction density is 1.71.
[0067] For Solution 6, refer to Solution 1. The difference lies in: the silicon negative electrode is spherical-like (spherical) coated with a conductive agent (same as Example 1), and the compaction density is 1.66.
[0068] The experimental results corresponding to different solutions are shown in Table 1.
[0069] Table 1
[0070]
[0071]
[0072] 1. As Figure 3 As shown, the SEM images of Schemes 4 and 5 clearly show that changing the morphology of the silicon negative electrode can increase the compaction density, and the particle integrity is higher, which helps to maintain good stability during the cycle.
[0073] 2. The rate performance is as follows:
[0074] 0.5C charge to maximum voltage 4.55V, 0.05C cut-off, sleep for 10min, 0.2C discharge to 3V, rate performance see Table 2 and Figure 4 .
[0075] Table 2
[0076] plan 0.2C 0.5C 0.7C 1C 1.2C 1.5C 2C Solution 2 100.0% 96.1% 94.5% 93.1% 92.4% 91.4% 89.7% Solution 4 100.0% 95.5% 93.5% 91.9% 91.9% 90.5% 88.1% Solution 6 100.0% 96.8% 95.5% 94.6% 94.0% 93.1% 91.6%
[0077] The rate performance of Scheme 2 is better than that of Scheme 4, which indicates that the rate performance of spherical silicon negative electrode is worse than that of amorphous silicon; the rate performance capacity retention rate of Scheme 6 is about 5% higher than that of Scheme 4, indicating that the surface coating of linear nanocarbon conductive agent significantly improves the conductive performance; the rate performance of Scheme 2 is about 2% higher than that of Scheme 4 at high rate, indicating that the spherical (spherical) silicon coated with linear nanocarbon conductive agent has better performance than amorphous silicon.
[0078] 3. The cycle performance is as follows:
[0079] Test format: 1C charge for 30 minutes, 0.7C charge to the maximum voltage of 4.55V, 0.05C cut-off, sleep for 10 minutes, 0.5CP discharge to 3V, cycle 200 times;
[0080] like Figure 5 As shown, it can be seen from the cycle curve that: capacity retention scheme 4 < scheme 2 < scheme 6, and stability scheme 6 is the best, indicating that the negative electrode sheet made of spherical silicon coated with linear nanocarbon conductive agent has the best performance.
[0081] Example 5
[0082] The lithium-ion battery prepared by using the above-mentioned negative electrode sheet is specifically prepared as follows:
[0083] 1) After the rolled positive electrode sheet and negative electrode sheet are cut and cut, the electrode tabs are welded to prepare the positive electrode sheet and negative electrode sheet to be wound;
[0084] 2) preparing an electrode group by winding the prepared positive electrode sheet, negative electrode sheet and separator;
[0085] 3) Encapsulate the electrode group in an aluminum-plastic shell for bilateral encapsulation;
[0086] 4) Dry the electrode group, test the electrode group for moisture, and then inject liquid;
[0087] 5) The electrode group after liquid injection is packaged, aged at room temperature for 36 hours, and subjected to formation, hot pressing, and capacity separation processes to complete the preparation of the battery.
[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention, which are all considered to be within the protection scope of the present invention.
Claims
1. A high withstand voltage lithium ion negative electrode plate, characterized in that: It is prepared by the following method: (1) Pulp graphite and silicon materials respectively according to the mixing ratio of the first coating 1 and the second coating 2. Among them, the raw materials of the first coating 1 are composed of graphite, silicon, binder and conductive agent, and the mass ratio of graphite + silicon: binder: conductive agent is 85-97: 2-8: 0.1-7; the raw materials of the second coating 2 are composed of graphite, silicon, binder and conductive agent, and the mass ratio of graphite + silicon: binder: conductive agent is 85-96: 2-10: 0.1-5; the mass ratio of graphite and silicon is 68-83: 9-24; (2) Use a double-layer coating method to simultaneously form the first coating 1 and the second coating 2 on the current collector 3, where the second coating 2 is located between the current collector 3 and the first coating 1; (3) Compact the electrode sheet through a rolling process.
2. The high withstand voltage lithium ion negative electrode plate according to claim 1, characterized in that: The graphite in step (1) uses graphite secondary particles, and the D10, D50, and D90 particle size distributions of the graphite secondary particles are 6μm < D10 < 12μm, 15μm < D50 < 17μm, and 35μm < D90 < 37μm respectively. The D10, D50, and D90 particle size distributions of the silicon particles are 4μm < D10 < 5μm, 6μm < D50 < 9μm, and 10μm < D90 < 13μm respectively.
3. The high withstand voltage lithium ion negative electrode plate according to claim 1 or 2, characterized in that: The silicon raw material in step (1) is spherical / spherical silicon with a conductive agent coated on the surface.
4. The high withstand voltage lithium ion negative electrode plate according to claim 1, characterized in that: In the first coating 1, the mass ratio of graphite + silicon: binder: conductive agent is 96.73: 3.04: 0.23; in the second coating 2, the mass ratio of graphite + silicon: binder: conductive agent is 96.39: 3.38: 0.23, and the mass ratio of graphite and silicon is 76:
18.
5. The high withstand voltage lithium ion negative electrode plate according to claim 1 or 4, characterized in that: The conductive agent is carbon nanotubes or linear nano-carbon conductive agent; the binder is composed of PAA, CMC-Li and SBR, and the mass ratio of PAA, CMC-Li and SBR is (10-49): (10-45): (51-90).
6. The high withstand voltage lithium ion negative electrode plate according to claim 5, characterized in that: The mass ratio of PAA, CMC-Li and SBR is 1: 1:
2.
7. The high withstand voltage lithium ion negative electrode plate according to claim 1, characterized in that: The material of the current collector 1 is a copper foil with a thickness of 4-15μm.
8. The high withstand voltage lithium ion negative electrode plate according to claim 1, characterized in that: The compaction density in step (3) is 1.62-1.
71.
9. A lithium-ion battery uses the high-voltage-resistant lithium-ion negative electrode sheet described in any one of claims 1-8 as the negative electrode sheet of the battery.
10. The lithium-ion battery according to claim 9, characterized in that: It is prepared by the following method: 1) After slitting and cutting the rolled positive electrode sheet and negative electrode sheet, weld the electrode tabs to prepare the positive electrode sheet and negative electrode sheet to be wound; 2) Prepare the prepared positive electrode sheet, negative electrode sheet and separator into an electrode assembly by winding; 3) Package the electrode assembly in an aluminum-plastic shell and perform double-sided packaging; 4) Dry the electrode assembly, inject electrolyte after testing that the moisture of the electrode assembly is qualified; 5) Package the electrode assembly after injecting electrolyte, age it at room temperature for 36h, and perform formation, hot pressing and grading processes to complete the preparation of the battery.
Citation Information
Cited By
Silicon-carbon negative plate, preparation method thereof and lithium ion battery
CN122158483A